Incidence of infective endocarditis and its thromboembolic complications in a pediatric population over 30 years. (1st February 2018) - Thom, K.; Hanslik, A.; Russell, J.L.; Williams, S.; Sivaprakasam, P.; Allen, U.; Male, C.; Brandão, L.R.
Abstract: Background: Pediatric infective endocarditis (IE) has been associated with high morbidity and mortality, mostly related to thromboembolic complications (TEC). The objective of our study was to describe the experience in children with IE and to review the changes over a thirty-year period, regarding origin of IE, incidence of vegetations, TEC and their respective morbidity and mortality rates. Methods: A retrospective chart review of children aged 0–18 years with IE defined by the Duke Criteria and admitted to The Hospital for Sick Children, was conducted. Data were divided into three periods (P); P1 (1979–1988); P2 (1989–1998); and P3 (1999–2008). Results: The study included 113 patients, median age 7 yrs.; females: 46 (41%), congenital heart defects 95 (84%), comparable in all periods. Overall, cardiac vegetations were found in 68/113 patients (60%); large vegetations (≥ 1 cm) in 32 patients (28%). Fourty-five (45/133 [40%]) TEC were documented, 22 patients (20%) developed cerebrovascular events (CVE) and 23 patients (20%) had non-CVE. Patients diagnosed during P3 were older, had more vegetations ( p  < 0.05), and a higher incidence of community acquired-IE (p < 0.05). Overall, mortality was 15%, comparable in all periods. Significant risk factors for mortality were vegetations (HR 6.44; 95% CI: 2.07–20.01, p = 0.002) and heart failure (HR 28.39; 95% CI: 10.49–76.85, p < 0.001). Conclusions: Over the study period, we report a growing incidence of community acquired pediatric IE in older children accompanied by an increasing rate of TEC. Heart failure and vegetations were associated with an increased mortality. These preliminary data need to be confirmed by prospective data. Highlights: Epidemiological changes of infective endocarditis over 30 years. Growing incidence of infective endocarditis in older children with more embolization. Heart failure and vegetations associated with mortality. Inreasing risk population due to improved treatment for congenital heart disease.